2016
DOI: 10.1007/s11881-016-0129-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of feedback and differences between good and poor decoders in a repeated word reading paradigm in first grade

Abstract: The direct, retention, and transfer effects of repeated word and pseudoword reading were studied in a pretest, training, posttest, retention design. First graders (48 good readers, 47 poor readers) read 25 CVC words and 25 CVC pseudowords in ten repeated word reading sessions, preceded and followed by a transfer task with a different set of items. Two weeks after training, trained items were assessed again in a retention test. Participants either received phonics feedback, in which each word was spelled out an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…It can be concluded that visual dictation was more efficient than word copying for learning to spell rule-based words and loan words, which complements the findings from previous research (e.g., Bosman, Van Huygevoort et al, 2006;Hilte & Reitsma, 2006, 2008. As the authors of earlier research concluded, spelling from memory increases the focus on orthographic details (e.g., Hilte & Reitsma, 2006, 2008Van Leerdam et al, 1998). Visual dictations leads to a quicker implementation of specified lexical representations than word copying, because with copying more repetitions are required to reach the same accuracy level for both word types.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…It can be concluded that visual dictation was more efficient than word copying for learning to spell rule-based words and loan words, which complements the findings from previous research (e.g., Bosman, Van Huygevoort et al, 2006;Hilte & Reitsma, 2006, 2008. As the authors of earlier research concluded, spelling from memory increases the focus on orthographic details (e.g., Hilte & Reitsma, 2006, 2008Van Leerdam et al, 1998). Visual dictations leads to a quicker implementation of specified lexical representations than word copying, because with copying more repetitions are required to reach the same accuracy level for both word types.…”
Section: Discussionsupporting
confidence: 82%
“…Repeated spelling training of rule-based words and loan words contributes to the construction of highly specified lexical representations (Perfetti, 1992(Perfetti, , 2017Shahar-Yames & Share, 2008). In several studies, it has been found that spelling training is particularly effective if a memory component is involved, as has been shown, for example, with visual dictation in Dutch (Bosman, Van Huygevoort et al, 2006;Hilte & Reitsma, 2006, 2008Van Leerdam et al, 1998), visual imagery in Spanish (Gaintza & Goikoetxea, 2016), and the so-called cover-copy-compare strategy in English (Cates et al, 2007;Nies & Belfiore, 2006).…”
Section: Repeated Spelling Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequently, dyslexic students exhibit significant alterations in morphological awareness (Layes et al, 2017), poorer phonological proficiency (Siddaiah & Venkatesh, 2014), and impaired general orthographic processing (Elbeheri et al, 2020;van Gorp et al, 2017) which lead to impaired reading processing (Tibi & Kirby, 2019).…”
Section: Discussionmentioning
confidence: 99%